A case study on comfort and efficiency of a selected school for the deaf in relation to deaf space design principles - Jim, Jazmine T.; Florendo, Raquel B. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
This study examined the comfort and efficiency of a selected private senior high school for the Deaf in Pasay City in relation to Deaf Space Design Guidelines. It was formulated from the idea that the Deaf are visually-centered people that possess high visual-spatial intelligence. The study aimed to explore whether or not Deaf Space Design Guidelines can enhance connections and articulation between users and to recommend design solutions for schools for the Deaf in the Philippines. This research was a descriptive in-depth case study. Purposive sampling was used to select the location, which required a learning environment that observes physical adjustments in order to better-suit the Deaf. It analyzed psychological and physical characteristics such as furniture layout, safety features, material finishes, color, maintenance, and activities done in the space. It applied triangulation through observations, interviews with key informants, focus group discussions, and survey questionnaires. Four to five weeks were spent on data collection. The Deaf school under this study adheres to the recommendations of the Deaf Space Design Guidelines formulated by the Gallaudet University in Washington D.C., with some modifications due to some limitations on space and cost. This study showed that applying certain adjustments to the physical environment can promote the wellbeing of Deaf users and maximize their full capabilities throughout their learning years. However, the result of this study also showed certain peculiarities in the preferences of the Deaf respondents particularly in terms of privacy, which may be attributed to cultural factors.
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Deaf -- Education -- Philippines -- Pasay City; Deaf culture -- Philippines -- Pasay City; Hearing impaired students; School buildings -- Philippines -- Pasay City -- Designs and plans